Nuestra América: o Nacionalismo Internacionalista de José Marti - Silva, Gislania de Freitas (2013)
This dissertation aims to present the singularities of the political thought of the Cuban revolutionary José Martí (1853-1895), focusing on the national and international aspects of his political project to Latin America. Having lived in the context of the expansion of the political economical dominance of the United States, Martí witnessed and documented in his personal letters and articles for newspapers the walk of the American continent into the new phase of Capitalism: the Imperialism. We will give special attention to the political peculiarities of the United States policies to its neighbors in the South and the proposals framed by José Martí for the emancipation of the Hispano-American republics. In this way, our emphasis will be on his project for the independence of Cuba and the definition, in his analytical frames and political agenda, of Nuestra América, and the urgent need to found and defend it, declaring its second independence.